2013
DOI: 10.1080/00288330.2013.815641
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance ofAbarenicola affinis(Arenicolidae, Polychaeta) in tidal inlets of Otago, New Zealand

Abstract: Lugworms are important members of the macrobenthos of sheltered intertidal sediments, and this study assessed the abundance and distribution of Abarenicola affinis in Otago, southern New Zealand. Using a faecal cast:lugworm ratio (1.00:1.09) revealed a patchy distribution across inlets, with an overall mean abundance of 11.1 individuals/m 2 (range: 3.8 to 21.3 individuals/m 2 ). Distribution patterns varied among inlets, with lugworms mostly confined to the high intertidal zone, but spread across all intertida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the generally low population density of A. affinis in southern New Zealand (e.g. compared with A. marina in north European tidal bays, Reise et al 2001;Goerlitz et al 2013) meant that individual numbers were low. Whereas previous studies have shown that lugworm populations are characterised by temporal stability (Flach and Beukema 1994), seasonal variation may occur, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the generally low population density of A. affinis in southern New Zealand (e.g. compared with A. marina in north European tidal bays, Reise et al 2001;Goerlitz et al 2013) meant that individual numbers were low. Whereas previous studies have shown that lugworm populations are characterised by temporal stability (Flach and Beukema 1994), seasonal variation may occur, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There, the species covers about 70 % of c. 4,700 km 2 tidal flat area with an average density of 20-40 individuals per m 2 and is considered a structuring agent of regional landscape-forming processes (Beukema 1976;Riisgard and Banta 1998;Reise et al 2010). In contrast, less is known about lugworm species in other regions of the world, including populations in small semi-enclosed tidal bays, where lugworms are less dominant and exhibit a more patchy distribution (Hobson 1967;Wilson 1981;Krager and Woodin 1993;Goerlitz et al 2013). Previous studies have shown that lugworm distribution in tidal bays can be limited to certain locations on the shore, which has been associated with changes in habitat type, e.g.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A substrate layer with a depth of 5 cm (grain size <0.5 mm) was implemented in each bed (Crane & Merz, ) and was transformed into inert material after incineration (723.15 ± 50 K for 24 hr) (Bischoff, ). Above the substrate, a layer of 4 cm of filtered seawater (pH = 7.74 ± 0.19; T ª = 291.7 ± 1.24 K; 36 psu) permanently covered the experimental units (Görlitz, ). Marine RAS sludge was added as 0.5%, 2%, 4% and 10% for each of the series of experimental beds, relative to the total inert substrate content.…”
Section: Sludge Characterization Of Yellowtail Kingfish Marine Recircmentioning
confidence: 99%